2015
DOI: 10.1186/s13256-015-0619-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved antioxidant status by omega-3 fatty acid supplementation in breast cancer patients undergoing chemotherapy: a case series

Abstract: IntroductionBreast cancer is the second leading cause of cancer death in women worldwide and the third most common cancer in India. Various studies have reported that chemotherapy reduces the antioxidant status in patients with cancer. A diet rich in omega-3 fatty acids has been shown to offer protection against breast cancer through various mechanisms. However, there are no reports suggesting a relationship between consumption of omega-3 fatty acids during chemotherapy and antioxidant status in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
0
17
0
3
Order By: Relevance
“…There have been reports that inflammation and nutritional status improved by intervention with fish oil administration. (7,21,22). As fish oil is rich in EPA and DHA, we therefore considered that an improved CRP and decreased serum AA/EPA ratio, or n-6/n-3 ratio could be reached by eating a diet with n-3 fatty acid, such as EPA and DHA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been reports that inflammation and nutritional status improved by intervention with fish oil administration. (7,21,22). As fish oil is rich in EPA and DHA, we therefore considered that an improved CRP and decreased serum AA/EPA ratio, or n-6/n-3 ratio could be reached by eating a diet with n-3 fatty acid, such as EPA and DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia can also be diagnosed by measuring the psoas muscle area (4,5). Although nutritional management of cancer patients to prevent and resolve sarcopenia has not been established, attention has been focused on the effects of fatty acid administration on cancer patients (6)(7)(8). Furthermore, studies that have identified a relationship between a significant decrease in psoas muscle volume and CRP increase in patients with cancer cachexia (9).…”
mentioning
confidence: 99%
“…In addition, Mansara et al [11] estimated in a case report on five Indian women with breast cancer that supplementation of fish oil significantly (p<0.01) increased SOD, GSH reductase, and CAT activity in red blood cells and the total plasma antioxidant status in the patients. They concluded that Omega-3 fatty acids might be an alternative adjuvant treatment for breast cancer instead of chemotherapy due to its antioxidant potential.…”
Section: Discussionmentioning
confidence: 99%
“…Mansara et al [11] reported that Omega-3 supplementation has the ability to significantly (p<0.01) increase antioxidant enzymes, superoxide dismutases (SOD), glutathione (GSH) reductase and catalase (CAT) enzymes, activity in red blood cells, and the total plasma antioxidant status in breast cancer patients undergoing chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, ω3 PUFAs are incorporated into the phospholipids of mitochondrial membranes and replace ω6 PUFAs in their composition, which explains the membraneprotective effect of ω3 PUFAs. On the other hand, ω3 PUFAs can activate the antioxidant cell protection link [26] in the liver of tumor-bearers.…”
Section: The Content Of Primary (A) Secondary (B) and Terminal (C)mentioning
confidence: 99%